ENT 300 : Crema Capulus / Nur Aisyah Annuar ... [et al.] - Annuar, Nur Aisyah; Samsuri, Muhamad Amirul Hafiz; Md Khotar, Nur Ainn; Mohd Noor, Nasrul Hakim; Mohd Azhar, Akbarulazfar (2019)
Dalgona coffee is a beverage made by whipping equal parts instant coffee powder, sugar, and hot water until it becomes creamy and then adding it to cold or hot milk. Occasionally, it is topped with coffee powder, cocoa, crumbled biscuits, or honey. It was popularized on social media during the COVID-19 pandemic, when people refraining from going out started making videos of whipping the coffee at home, by hand without using electrical mixers. The name is derived from dalgona, a Korean sugar sweet, due to the resemblance in taste and appearance, though most dalgona coffee doesn't contain dalgona. Just like any regular coffee, dalgona coffee can improve energy levels, making people feel less tired and smarter. In fact, instant coffee contains several antioxidants and nutrients that may benefit health in numerous ways, including a reduced risk of type 2 diabetes and liver disease. The instant coffee delivered a burnt taste and after mixing the whipped topping with the milk base, we found that, even diluted, the instant coffee was overpowering. We'll admit that the Dalgona coffee drink is simple to make, creative and aesthetically pleasing, but the taste falls short. Though there are many other companies that sells Dalgona’s, our company has been planning to make changes of our menu which will attract attention of people who loves caffeine. As we are in term of lockdown, our company decides to sell it online, which we will be posting all the ready-made dalgona items for customers and they just need to pour on the coffee and put in whip cream on top of it. It is more likely saving their time by not making it themselves.